Performance Development and Business Restructuring at PT. Adhya Tirta Batam - Tamrin Reni, Agus; Jane Wijaya, Della; Wicaksono, Wahyu; Hermawan, Febrian; Verina, Verina (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to analyse the process and impact of restructuring at PT Adhya Tirta Batam (ATB). This research uses qualitative research. Data collection is done through direct observation and documentation. The analysis technique used to analyse the process and impact of restructuring that occurred at PT Adhya Tirta Batam (ATB) was Strength, Weakness, Threat, and Threat (SWOT) analysis. The results of the analysis of the process and impact of restructuring that occurred at PT Adhya Tirta Batam (ATB) are: 1) Process Analysis: Since ATB underwent restructuring, ATB has continued to improve its performance to become one of the best water companies in Indonesia. Even though ATB's performance is not only recognised nationally but also internationally, 2) Impact Analysis: After restructuring, the quality and performance of the company have improved. Since 2010, ATB's water leakage rate has continued to decline, with an average of 15.28% per year. This is supported by the company's innovation strategy related to the use of appropriate technology to detect water pipes owned by ATB.